Development of Mobile Learning-Based Learning Media for Rhyming Materials at SDIT Wildan Mukholladun Blitar Regency - Permadani, Sholihatuzumna Putri; Muzaki, Ferril Irham; Mudiono, Alif (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to develop a poem learning media based on Mobile Learning designed for fifth-grade elementary school students. The method employed is research and development (R&D) using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The media was created using Google Sites and accessed via QR codes, containing learning materials, instructional videos, and assessment tools. Validation by content experts, media specialists, and teachers indicated that the media is highly suitable for use in learning. The results of validation from material experts obtained a percentage of 93.75%, the validation of media experts obtained a percentage of 85%, and validation by users obtained an average percentage of 94.3%. The small-scale practicality trial obtained a percentage of 100%, then the large-scale trial obtained a percentage of 98.8% where p = both were included in the "Very Practical" category. Practicality tests on both small and large scales showed excellent results, with high levels of usability and engagement. The media was found to be effective in enhancing students’ interest and understanding of poem material, while also offering an enjoyable and interactive learning experience.